THE EFFECT OF BRAND IMAGE, PRODUCT QUALITY, PRICE ON CONVERSE SHOE PURCHASE DECISION IN WEST CIKARANG - Basar Maringan Hutauruk; Suryadi Suryadi (Utan Kayu Publishing, 2026)
Purchasing decisions are an important aspect of a marketing strategy that reflects a product's success in attracting interest and meeting consumer needs. This study aims to determine the influence of brand image, product quality, and price on purchasing decisions for Converse shoes in West Cikarang. This study uses a quantitative method with data collection techniques through distributing questionnaires to respondents. The sample in this study amounted to 100 respondents, determined using the Lemeshowmethod. The sampling technique used was nonprobability sampling with a purposive sampling approach.Data processing was carried out using the SPSS version 27 application. The results of the study indicate that partially and simultaneously, the variables of brand image, product quality, and price have a positive and significant effect on purchasing decisions. This means that the better the brand image, the higher the product quality, and the more appropriate the price offered, the more likely consumers are to decide to purchase the product. These findings have implications for companies in improving marketing strategies, particularly in maintaining brand image, maintaining product quality, and setting prices that are in accordance with the value received by consumers. Keywords: Brand Image, Product Quality, Price, Purchase DecisionJEL Code: